2012
DOI: 10.1590/s0100-40422012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradação de paclobutrazol por Pseudomonas spp. em sistemas de solo saturados

Abstract: Recebido em 28/6/11; aceito em 6/12/11; publicado na web em 28/2/12 BIODEGRADATION OF PACLOBUTRAZOL IN SATURATED SOIL SYSTEMS BY Pseudomonas spp. Paclobutrazol is growth regulator of plants that has low mobility in soil and therefore has accumulated. The objective of this study was to investigate the paclobutrazol biodegradation in two soils from the São Francisco River Valley. The biodegradation experiments were conducted in batch using paclobutrazol and paclobutrazol added glycerol. The experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…In experiments with addition of inoculum, the biodegradation was 38 % and 29 %, in soils A and B, respectively. Vaz et al [ 2 ], found about 43 % biodegradation, after 14 days, when added the same inoculum. Higher biodegradation observed by these authors was due to experiments to be in saturated soils.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In experiments with addition of inoculum, the biodegradation was 38 % and 29 %, in soils A and B, respectively. Vaz et al [ 2 ], found about 43 % biodegradation, after 14 days, when added the same inoculum. Higher biodegradation observed by these authors was due to experiments to be in saturated soils.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Paclobutrazol (PBZ) is a plant growth retardant of broad spectrum with great use potential for agronomic and ornamental crops [5] [6]. It acts inhibiting gibberellin synthesis, reducing plant growth, and promoting flower and fruit production [7]. Its mode of action has usually favored orchid acclimatization as it reduces transpiration, plant height, biomass, and leaf area, besides improving plant stomatal resistance; however, further studies on organ formation are still needed [8].…”
Section: Introductionmentioning
confidence: 99%
“…After 15 days of pickling, bacterial composition was mainly rich in Lactobacillus , which evidenced that the composition of the bacterial community could be changed as the pickling progressed. Remarkably, Pseudomonas and Serratia could be identified during the pickling process, and both of them have been confirmed to degrade paclobutrazol in previous studies 22,23 . Therefore, the reason for the degradation of paclobutrazol might be attributed to the presence of related degrading bacteria and whether the stereoselective behaviors between two isomers were related to these two bacteria required further verification.…”
Section: Resultsmentioning
confidence: 80%
“…Remarkably, Pseudomonas and Serratia could be identified during the pickling process, and both of them have been confirmed to degrade paclobutrazol in previous studies. 22,23 Therefore, the reason for the degradation of paclobutrazol might be attributed to the presence of related degrading bacteria and whether the stereoselective behaviors between two isomers were related to these two bacteria required further verification. The relative abundances of fungi were investigated by ITS sequencing technology.…”
Section: Analysis Of 16-s Rrna and Its Sequencingmentioning
confidence: 99%